DESAIN TERAS DAN BAHAN BAKAR PLTN JENIS PEBBLE BED MODULAR REACTOR (PBMR) DENGAN MENGGUNAKAN PROGRAM SRAC - Santoso, Sungkowo Wahyu; Widiharto, Andang; Sardjono, Yohannes (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Core and fuel down scale analysis on PBMR-HTR using SRAC program aims to identify the influence of U235 enrichment, burnable poison, coolant flow rate and coolant temperature entered to criticality core and safety aspects of nuclear reactor with the parameters are multiplication factor (keff) and fuel temperature coefficient, moderator temperature coefficient and coolant temperature coefficient. Core PBMR-HTR finite cylindrical with a hole in the middle which contains 334,000 pebble fuel bed. That consist of UO2 fuel, graphite moderator and helium coolant. Down scale the design model performed on the half core represent the whole core. The study was conducted by varying the fuel enrichment of 8%; 8.5%; 9%; 9.5% and 10%, while variation burnable poison enrichment at 5 ppm, 7 ppm, 9 ppm, 11 ppm and 15 ppm. The variation of coolant flow rate of 60%, 80%, 100%, 120% and 140% from its original value at 17.118 kg/s while the variation of coolant temperature input at 673.15 K; 723.15 K; 773.15 K; 823.15 K and 873.15 K. In this research, value of keff without Gd2O3 are 1.026213 (BOL) and 1.004173 (EOL) with excess reactivity of 2.55% with 9% U235 enrichment. While keff on BOL by using 7 ppm Gd2O3 of 1.006968 and 1.004198 for EOL with excess reactivity of 0.69%. Fuel temperature reactivity coefficient, moderator and coolant in a row for -8.597317E-05/K; -2.595284E-05 /K and 1.1496E-06/K. Temperature reactivity coefficient is negative. This indicates inherent safety characteristic have been met. Increasing the input temperature and coolant flow rate reduction lowers the value of keff core, and it will contribute to negative reactivity coefficient.